The Application of Cooperative Learning Model With Teams Games Tournament Type On the Seventh Grade Students In Social Arithmetic - Hikmah Nurul Hidayah (Universitas Islam Jember, 2020)
The purpose of this study was to determine the results of the application of the Teams Games Tournament (TGT) type of cooperative learning model as seen from the teacher's ability to manage learning, student activities, learning outcomes and student response results. This research design uses One-Shot Case Study. The sample used in this study was class VII C, amounting to 28 students. The data analysis technique was carried out using the method of obesity, test methods, and student questionnaire responses. Data analysis techniques that describe the results of the teacher's ability to manage learning, student activity data, learning outcome data and student response results data. Based on the results of research on the implementation of the Teams Games Tournamnet (TGT) type of cooperative learning model on social arithmetic material, 1) the ability of the teacher to manage the cooperative learning model of the Teams Games Tournament (TGT) gets an overall score of 4.1 with a very good category, 2) student activities with the application of learning models using the Teams Games Tournament (TGT) obtained an overall score of 55, 5 with a fairly active category, 3) overall student learning outcomes reached 78.57% complete student grade scores, 4) the results of student responses using the TGT learning model overall reached positive with a value of 83.21% Keywords: teams games tournament, aritmetika sosial